ANALYSIS OF THE ETIOLOGICAL STRUCTURE AND ANTIBIOTIC SENSITIVITY OF INFECTIOUS AGENTS ASSOCIATED WITH MEDICAL CARE IN SURGICAL HOSPITALS - Воробьева, Ольга Николаевна; Дулепо, Светлана Александровна; Несвет, Татьяна Геннадьевна; Жилина, Наталья Михайловна (Medicine in Kuzbass, 2022)
Knowledge of the structure of wound and SMP pathogens and regular monitoring of the dynamics of their resistance to antimicrobial drugs makes it possible to effectively combat purulent-inflammatory complications, optimize empirical and etiotropic therapy. The aim of the research – study of the etiological structure and profile of antibiotic resistance of wound infection pathogens Material and methods. The results of a cultural study of 4152 samples of biomaterial in patients of surgical departments of the multidisciplinary Clinical Hospital N 1 of Novokuznetsk 2018-2021 were analyzed. The classical bacteriological method and the BD BACTEC FX microbiological analyzer were used. Results. 5009 strains of microorganisms were isolated: 36 % in monoculture and 64 % in various associations. The leading pathogens are representatives of gram-negative microflora: Klebsiella, E. coli, Pseudomonas aeruginosa, Acinetobacter spp. High-risk pathogens of priority include enterococci and Staphylococcus aureus. There is an increase in the specific gravity and species diversity of microbial associations, among which enterococci and representatives of the Enterobacteriaceae family absolutely dominate. When studying the resistance profile of enterobacteria, Esherichia coli had the greatest sensitivity to antibiotics. Hospital strains of Klebsiella are resistant to beta-lactams. The drug of choice may be amikacin. Isolates of Staphylococcus aureus are sensitive to almost all studied antibiotics, and enterococci are sensitive to vancomycin and linezolid. Pseudomonas аeruginosa and Acinetobacter spp. had multiple drug resistance. The most active against Pseudomonas aeruginosa are polymyxin B, ceftazidime and amikacin, and netilmycin. Acinetobacter spp. remained sensitive to cefoperazone-sulbactam, tigecycline and carbapenems. Therefore, effective treatment of purulent-inflammatory infections caused by non-fermenting gram-negative bacteria is impossible without taking into account epidemiological data on their antibiotic resistance. Conclusion. Data on the etiological structure and profile of antibiotic resistance of pathogens are of fundamental importance for substantiating adequate treatment and prevention of infectious complications in surgical hospitals.